(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article discusses the revision of a history honours historiography module. It discusses the rationale, methodologies and material used to respond to the imperative of curriculum transformation and decolonisation. The article is titled ‘testing transformation and decolonisation’ to emphasise the exploratory nature of this revision, but also to underline the challenging nature of teaching new material, which educators have often not been taught themselves. The article draws on the University of Pretoria’s 2016 Curriculum Transformation Framework document and narrates the practical challenges of implementing its recommendations. The article also provides a personal perspective of my embrace of calls for transformation and decolonisation of the university, which highlights the continuities I see in these contemporary calls with the historical concerns of the previous generations of progressive South African scholars who similarly called for and worked to realise a decolonisation of knowledge.